Exploring the Pharmacological Mechanism of the Effective Chinese Medicines Against Gynecological Cancer Based on Meta-Analysis Combined With Network Pharmacology Analysis - Ren, Ning; Yu, Lulin; Qian, Lihui; Ye, Gewei; Zhu, Zhenzheng; Yu, Jieru; Sun, Leitao; Zhang, Leyin (Frontiers in Oncology, 2022)
This meta-analysis plus network pharmacology aimed to investigate whether traditional Chinese medicine (TCM) combined with chemotherapy is associated with more beneficial efficacy data in the treatment of gynecological cancer (GC). A total of 11 randomized controlled trials (RCTs) consisting of 863 GC patients were included. Results showed a better ORR (RR: 1.42, 95% CI: 1.18–1.71; I2 = 21.4%; p = 0.282), DCR (RR: 1.13, 95% CI: 1.03–1.25; I2 = 0.0%; p = 0.492), PD (RR: 0.27, 95% CI: 0.11–0.65, p = 0.003; I2 = 0.0%, p = 0.930), and QOL (SMD: 0.85, 95% CI: 0.38–1.33, p = 0.005) and higher proportions of CD3+ T (WMD: 5.65, 95% CI: 4.23–7.08, p = 0.000; I2 = 68.3%, p = 0.004), CD4+ T (WMD: 6.97, 95% CI: 5.35–8.59, p = 0.000; I2 = 83.4%, p = 0.000), and the CD4+/CD8+ T ratio (WMD: 0.32, 95% CI: 0.23–0.42, p = 0.000; I2 = 78.0%, p = 0.000). The number of adverse events (AEs) was significantly lower in the TCM + chemotherapy group. The active components and targets of 19 high-frequency Chinese medicines obtained from the meta-analysis were screened and explored in network pharmacology analysis. Also, a regulatory network of active components and targets, a core network and key genes, a diagram of protein interaction, network topology analysis, and gene body GO function and KEGG pathway enrichment analysis were performed. A total of 120 active components were identified. NPM1 and HSPA8 are the most critical target proteins in the core network of protein interaction. HSP90AA1 is the most important target protein in the TCM group. KEGG enrichment analysis showed that it was highly significant in the lipid and atherosclerotic pathways. Therefore, moderate evidence revealed that TCM plus chemotherapy has obvious advantages over chemotherapy alone in terms of tumor responses, QOL, peripheral blood lymphocyte levels, and fewer AEs in the treatment of GC. The potential important targets and core genes were displayed. Systematic Review Registration www.crd.york.ac.uk/PROSPERO/, identifier CRD42021252500.